1995
DOI: 10.1111/j.1600-0625.1995.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azelaic acid on melanoma cells in culture

Abstract: Using a clonogenic assay in vitro, it has been shown that exposure to azelaic acid (1-100 mM) for 24 hours has a dose-dependent effect on the survival of the colony-forming ability of murine (B16) and human (HMB2, and SK23) melanoma cells as compared with a non-melanotic non-tumoral Chinese hamster cell line (CHO). Both human cell lines were more sensitive to the diacid than the murine cells, and the HMB2 cells were more sensitive than the SK23 cells. These differences may be partly correlated with differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Melanin inhibition in melanoma cells [132]. Clinical study on patients with facial hyperpigmentation showed an improvement in pigment intensity by one or more grades [133].…”
Section: Azelaic Acidmentioning
confidence: 99%
“…Melanin inhibition in melanoma cells [132]. Clinical study on patients with facial hyperpigmentation showed an improvement in pigment intensity by one or more grades [133].…”
Section: Azelaic Acidmentioning
confidence: 99%
“…The substances that have a pigment inhibitory effect in the hyperpigmented lesions include retinoid, kojic acid, arbutin, hydroquinone, pentadecenoic acid, oleanolic acid, ursodeoxycholic acid, vitamin C, catechol, phenol, medimin C, and pinellia ternata extract 19 . Drugs that act by both suppression of melanocytes proliferation and melanogenesis include 4-isopropylcatechol, 4-hydroxyanisole, hydroquinone, monobenzylether of hydroquinone, monoethylether of hydroquinone, and azelaic acid [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that topical application of 0.2% phytoclear-EL1 on human skin had a similar inhibitory effect of pigmentation as the positive control (3% arbutin). Recently, the combined use of hydroquinone, azelaic acid, and retinoic acid has been reported to be effective in inducing a pigment inhibitory effect 8,20 . Thus, applying phytoclear-EL1 with arbutin, kajic acid, and retinoic acid is thought to be effective and presents an interesting area for continued research.…”
Section: Discussionmentioning
confidence: 99%
“…AzA can block tyrosinase activity by competitive inhibition [67,68,69,70,71]. AzA is also reported to have an inhibitory effect on DNA synthesis in melanoma cell lines [71,72].…”
Section: Influence Of Aza On Melanogenesismentioning
confidence: 99%